THE INFLUENCE OF SOCIAL MEDIA MARKETING AND BRAND AWARENESS ON PURCHASE INTENTION WITH BRAND IMAGE AS A MEDIATING VARIABLE AT ADIWANA RESORT JEMBAWAN UBUD - Cecilia Dea Natasha Setiawan; Ni Putu Intan Ananda Putri; Ni Nyoman Anjali Seruni (SOSIOEDUKASI, 2026)
The present research examines the impact exerted by social media marketing and brand awareness on purchase intention, wherein brand image operates as an intervening construct, focusing on Adiwana Resort Jembawan, a four-star wellness boutique establishment located in Ubud, Bali. Despite active Instagram marketing and strong brand awareness metrics, the resort experienced persistently low consumer purchase intention, reflected in unmet room booking targets and declining website visits between 2019 and 2021. This contradiction motivated an investigation into the interrelationships among the four variables. A quantitative research framework was utilized, wherein data were obtained from 115 Instagram followers of the resort, selected through purposive sampling, using Likert-scale questionnaires. Subsequent analysis was performed employing Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.3.3. The investigation substantiates seven significant positive associations: social media marketing and brand awareness each exert a positive influence on both purchase intention and brand image; brand image positively affects purchase intention; and brand image serves as a mediator in the relationships connecting both independent variables to purchase intention. The model shows strong predictive relevance (Q² = 0.895). To boost bookings, Adiwana Resort Jembawan should improve Instagram accessibility, share consistent product information, and create engaging content. Future research should include other locations and additional variables to enhance generalizability.